ANALISIS NILAI TAMBAH AGROINDUSTRI PENGOLAHAN KOPI ARABIKA EKSPOR DI KABUPATEN ACEH TENGAH (STUDI KASUS PADA KSU SARA ATE) - Peggi Epaga; Akhmad Baihaqi; Muji Burrahmad; Elly Susanti (Departemen Sosial Ekonomi Faperta Unpad, 2019)
AbstrakPenelitian ini bertujuan untuk mengetahui seberapa besar agroindustri pengolahan kopi arabika ekspor pada KSU Sara Ate di Kabupaten Aceh Tengah dapat menciptakan nilai tambah untuk kopi dan untuk mengetahui apakah sudah efesien pemasaran kopi arabika ekspor pada KSU Sara Ate di Kabupaten Aceh Tengah. Penentuan lokasi penelitian ini ditentukan secara sengaja (Purposive) dengan pertimbangan karena industri pengolahan kopi ini berproduksi secara berkesinambungan dan juga merupakan salah satu industri pengolahan kopi di Aceh Tengah. Metode analisis yang digunakan pada penelitian ini adalah metode analisis nilai tambah model hayami dan metode analisis efesiensi pemasaran. Hasil analisis menunjukkan nilai tambah kopi arabika ekspor green bean grade 1 (spesialty) pada KSU Sara Ate sedang, dan green bean grade 2 (premium) rendah. Berdasarkan nilai efesiensi pemasaran green bean grade 1 dan green bean grade 2 pada KSU Sara Ate pemasaran dinilai efesien. Nilai tersebut memenuhi syarat ketentuan dimana jika EP 0-50 % pemasaran dinilai efesien.AbstractThis study aims to find out how big arabica coffee processing export agroindustry in KSU Sara Ate in Central Aceh Regency can create added value for coffee and to know whether it has efficient marketing arabica coffee export at KSU Sara Ate in Central Aceh regency. Determination of the location of this study is determined purposively (Purposive) with consideration because the coffee processing industry is producing continuously and is also one of the coffee processing industry in Central Aceh. The method of analysis used in this research is the value added analysis method of hayami model and marketing efficiency analysis method. The analysis result shows the value of arabica coffee export of green bean grade 1 (specialty) on KSU Sara Ate being, and green bean grade 2 (premium) low. Based on the value of marketing efficiency of green bean grade 1 and green bean grade 2 on KSU Sara Ate marketing is considered efficient. The value is eligible provisions where if 0-50% EP marketing is considered efficient.Keywords: Value-added, Marketing Efficiency, Arabica Export Coffee AbstractThis study aims to find out how big arabica coffee processing export agroindustry in KSU Sara Ate in Central Aceh Regency can create added value for coffee and to know whether it has efficient marketing arabica coffee export at KSU Sara Ate in Central Aceh regency. Determination of the location of this study is determined purposively (Purposive) with consideration because the coffee processing industry is producing continuously and is also one of the coffee processing industry in Central Aceh. The method of analysis used in this research is the value added analysis method of hayami model and marketing efficiency analysis method. The analysis result shows the value of arabica coffee export of green bean grade 1 (specialty) on KSU Sara Ate being, and green bean grade 2 (premium) low. Based on the value of marketing efficiency of green bean grade 1 and green bean grade 2 on KSU Sara Ate marketing is considered efficient. The value is eligible provisions where if 0-50% EP marketing is considered efficient.Keywords: Value-added, Marketing Efficiency, Arabica Export Coffee